Predictors of admission to an assertive outreach service for psychosis in Lebanon - Ghida Kassir; Samer El Hayek; Raghid Charara; Michele Cherro; Hala Itani; Joseph El Khoury (Public Library of Science (PLoS), 2022)
Schizophrenia is a chronic, debilitating mental illness that contributes significantly to the global burden of disease. Assertive outreach treatment for patients with schizophrenia and psychotic disorders has been implemented to improve treatment adherence and outcomes. The suitability of this model of care outside the western context has not been fully established. We describe the characteristics of 45 patients enrolled in the Psychosis Recovery Outreach Program (PROP), a program developed at a leading psychiatric facility in Lebanon. We collected twelve-month data for patients and used logistic regression models to identify predictor variables for enrollment in the service compared to those receiving standard treatment. Patients were mostly males (77.8%), younger than 39 years (80%), of college or higher education (68.2%), and diagnosed with schizophrenia (46.7%) or schizoaffective disorder (48.9%). About one-quarter (22.7%) had a comorbid cannabis use disorder. A majority received more than one oral antipsychotic (75.6%) while half (51.1%) were maintained on a long-acting injectable (LAI) antipsychotic. The following variables were significant predictors of enrollment in PROP: having a comorbid cannabis use disorder (OR 2.83 [1.25 - 6.37]), being prescribed a LAI antipsychotic (OR 9.99 [4.93-20.24]) or more than one oral antipsychotic (OR 4.57 [2.22-9.39]), visiting the emergency department more than once (OR 8.7 [2.64-28.68]), and admission to the psychiatry unit (OR 13.91 [3.17-60.94]). In addition, those following up in PROP were younger and less likely to be in the oldest age group (over 54 years) [OR 0.11 (0.01-0.93)], less likely to be females (OR 0.39 [0.18-0.81]), and less likely to be diagnosed with "other psychotic disorder" as compared to schizophrenia (OR 0.14 [0.03 - 0.62]). Our findings highlight that the assertive outreach model of care is applicable to its target population in the context of psychiatric care in Lebanon, namely young individuals with psychosis, higher comorbidities and a severe course of illness.